Compiling a Corpus for Teaching Medical Translation - Elizabeth de la Teja Bosch; Ania Mercedes Carballosa González (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2014)
Background: medical translation has countless documentary sources; the major difficulty lies in knowing how to assess them. The corpus is the ideal tool to perform this activity in a rapid and reliable way, and to define the learning objectives based on text typology and oriented towards professional practice. Objective: to compile an electronic corpus that meets the requirements of the professional practice to perform specialized medical translation. Methods: a pedagogical research was conducted in the province of Cienfuegos. The units of analysis involved records from translators of the Provincial Medical Sciences Information Center and specialized translators in this field, who completed a questionnaire to accurately determine their information needs, conditioning the corpus design criteria. The analysis of a set of texts extracted from highly reputable sources led to the text selection and final compilation. Subsequently, the validation of the corpus as a documentary tool for teaching specialized medical translation was performed. Results: there was a concentration of translation assignments in the topics: malignant tumors, hypertension, heart disease, diabetes mellitus and pneumonias. The predominant text typologies were: evaluative and dissemination of current research, with plenty original articles and reviews. The text corpus design criteria were: unannotated, documented, specialized, monitor and comparable. Conclusions: the corpus is a useful tool to show the lexical, terminological, semantic, discursive and contextual particularities of biomedical communication. It allows defining learning objectives and translation problems. Key words: teaching; translating; medicine